2013
DOI: 10.1002/ppul.22657
|View full text |Cite
|
Sign up to set email alerts
|

Nanomedicine as an innovative therapeutic strategy for pediatric lung diseases

Abstract: Nanomedicine is a rapidly emerging technology and represents an innovative field for therapy. Nanomaterials have intrinsically defined features for biomedical applications due to the high specific surface area, the amazing diversity, versatility in structure and function and the possibility of surface charge. In particular, the functionalization of targeting or stimuli-responsive unit on the surface of these materials gives them specific targeted therapeutic properties. There are many pediatric lung diseases t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 165 publications
(256 reference statements)
0
5
0
Order By: Relevance
“…This system remained in solution at room temperature and physiological pH, but changed into gel upon heating at physiological temperature, thus undergoing a heat‐induced gelation. Due to its rheological properties, biocompatibility, low toxicity, and structural similarity to natural glycosaminoglycans, chitosan hydrogels has found many biomedical applications, including tissue engineering and repair of cartilage, intervertebral disc and bone, as well as drug delivery systems . Recently, it was also shown to be a potential candidate for the embolization of blood vessels .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This system remained in solution at room temperature and physiological pH, but changed into gel upon heating at physiological temperature, thus undergoing a heat‐induced gelation. Due to its rheological properties, biocompatibility, low toxicity, and structural similarity to natural glycosaminoglycans, chitosan hydrogels has found many biomedical applications, including tissue engineering and repair of cartilage, intervertebral disc and bone, as well as drug delivery systems . Recently, it was also shown to be a potential candidate for the embolization of blood vessels .…”
Section: Introductionmentioning
confidence: 99%
“…Due to its rheological properties, biocompatibility, low toxicity, and structural similarity to natural glycosaminoglycans, 4 chitosan hydrogels has found many biomedical applications, including tissue engineering and repair of cartilage, intervertebral disc and bone, as well as drug delivery systems. [6][7][8][9] Recently, it was also shown to be a potential candidate for the embolization of blood vessels. 10,11 Blood vessel embolization is a minimally invasive procedure that is increasingly being used for treatment of a wide range of conditions such as palliative cancer therapy (that is, trans-arterial embolization (TAE), the treatment of vascular malformations, or to treat or prevent endoleaks following endovascular aneurysm repair (EVAR).…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles are generally considered as the particles of 1-100 nm in at least one dimension Mohamed and Xing 2012;Tian et al 2013;Xing et al 2010). As the size of the particles decreases, the surface area to volume ratio of nanoparticles increases considerably, this leads to trivial changes in their physicochemical and biological properties.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an imbalance between the generation of ROS and the detoxification capability of reactive intermediates by the cells causes oxidative stress . Although phytochemicals participated in a major role in reducing oxidative stress by inhibiting the ROS production, however, due to the solubility in water and thermal instability of such phytochemicals, nanotechnology plays an important role in enhancing the bioavailability of plant secondary metabolites due to their high biodegradability, biocompatibility, and slow drug release mechanism. Over the past decades, nanotechnology has been extensively used in medicines and has made a huge impact in medicinal sciences. This emerging field has wide applications in anticancer, antiviral, anti-HIV, and so on. Preparation of gold nanoparticles includes various chemical, physical, and biological methods. In the preparation of gold nanoparticles in addition to chemical and physical methods, the plant extract is used for the preparation of nanoparticles, which is considered the simplest, eco-friendly, and cost-effective approach. , More recently, green synthesis of metal nanoparticles furnishes the effective utilization of natural compounds in plant extracts, which can act as an excellent reducing agent for the conversion of a metal salt to a nanoparticle. Aromal et al reported the green synthesis of gold nanoparticles by photochemical preparation of seed particles from Macrotyloma uniflorum, and another photochemical preparation of seed particles was reported .…”
Section: Introductionmentioning
confidence: 99%